Diffusion-weighted magnetic resonance imaging in evaluating malignant lymph node invasion in patients with female genital neoplasms - Basta Nikolić, Marijana; Nikolić, Dragan; Stojanović, Sanja; Djurdjević, Srdjan; Nikolić, Olivera; Till, Viktor (Vojnosanitetski pregled, 2022)
Background/Aim. Functional imaging, including diffusion-weighted magnetic resonance imaging (DWI MRI) and apparent diffusion coefficient (ADC) map, provides promising results in discrimination benign from malignant pelvic and inguinal lymph nodes in patients with gynecological malignancies. The aim of the study was to assess diagnostic performances of DWI in differentiation between benign and malignant pelvic and inguinal lymph nodes in patients with gynecological malignancies. Methods. The prospective clinical study was conducted at the Clinical Center of Vojvodina, Serbia, from 2013 to 2016, comprising 80 patients with malignant gynecological tumors. Preoperatively, all patients underwent MRI examination, followed by standard surgical treatment with complete pelvic and/or inguinal lymphadenectomy. A combination of ADC value criteria and size-based criteria yields MRI the following diagnostic performances in discrimination between benign and malignant lymph nodes: sensitivity 95%, specificity 92%, overall accuracy 92.5%, positive predictive value 46%, and negative predictive value 99.6%. Histopathological examination of surgically removed material and lymph nodes separated in pelvic and inguinal anatomic groups was performed after the surgery. Results. A total of 2,320 lymph nodes were mapped and histopathologically examined in 80 patients included in the study. Metastases in lymph nodes were histopathologically confirmed in 28 (35%) patients. Measured ADC values were significantly lower in metastatic (mean ± standard deviation (SD), ADC: 0.8725 × 10-3 ± 0.0125 × 10-3 mm2/s) than benign lymph nodes (mean ± SD, ADC: 1.116 × 10-3 ± 0.1848 × 10-3 mm2/s; p = 0.001). If ADC value of 0.860 × 10-3 mm2/s was determined as a cut-off value for discrimination between benign and malignant lymph nodes, DWI sensitivity was 89%, specificity 85%, and overall accuracy was 86%, positive predictive values 30%, and negative predictive value 99%. Conclusion. DWI MRI sequence is a fast, simple, non-invasive method that aids significantly to MRI diagnostic performances in discrimination between benign and malignant pelvic and inguinal lymph nodes.
Keywords: diagnosis, differential; diffusion magnetic resonance imaging; genital neoplasms, female; lymph nodes; lymphatic metastasis; magnetic resonance imaging.